Effects of Fire Frequency Regimes on Flammability and Leaf Economics of Non-Graminoid Vegetation - Lamounier Moura, Arthur; Negreiros, Daniel; Fernandes, Geraldo Wilson (Fire (Basel, Switzerland), 2023)
Fire is an ecological factor that strongly influences plant communities and functional traits. Communities respond differently to fire, either decreasing or increasing in flammability and resource acquisition strategies. This study aimed to investigate the influence of fire over traits associated with flammability and the plant economic spectrum in a stressful and infertile mountainous grassland located in the Espinhaço mountain range in Brazil. Non-graminoid plant species were sampled in 60 5 m × 5 m plots distributed in three fire frequency categories. We measured several traits related to flammability—leaf dry matter content (LDMC), twig dry matter content, leaf area, bark thickness, branching architecture, plant height, leaf toughness (LT), and specific leaf area (SLA). Traits responded differently to the increase in fire frequency. For instance, the LDMC and LT were lower while the SLA was higher at high fire frequencies, indicating a trend towards reduced heat release and fire residence time. This shift resulted in the dominance of plants with a relatively more acquisitive strategy. This study brings evidence that traits respond coordinately towards a reduction of flammability with the increase in fire frequency and are strong indicators of the filtering role that fire plays as a disturbance on rupestrian grassland vegetation.